New media, cultural imperialism and the Malay muslim society in Malaysia - Mohamed, Shafizan (2020)
The Malay Muslims are the majority of the Malaysian population. They are the products of the Malaysian government’s institutionalization of Islam that was intended to create modern Malay Muslims that are economically savvy, religiously conservative and politically subservient. The Malaysian media system has been strictly protected to ensure that media content do not go too far against the state’s Islamic ideology. In fact, Malaysia has one of the most flourishing Islamic media industries where media channels, operations and content comply with the Syariah. However, the onslaught of new global media is changing this dynamic. While the distinction between the ‘old media’ and the ‘new media’ is becoming vague, this article argues that when discussing the impact of media, the term ‘new media’ is still relevant especially when trying to compare the changes in media effects. When analysing the impact of television for example, one can distinguish the differences between watching traditional TV boxes with streaming TV channels online. The former can be considered ‘old media’ while the latter is the ‘new media’. Taking this consideration as its basis, this commentary focuses on the implications of ‘new media’ such as social media, mobile applications and online streaming services on the Malay Muslim specifically and indigenous cultures generally. The commentary suggests that while the new media offers much opportunity for the Malay Muslims to be part of the contemporary world, it also reignites old concerns of cultural imperialism and troubling postmodern ideals.